(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Remarks about Pammene suspectana (Lienig & Zeller, 1846) and Dichrorampha infuscata (Danilevsky, 1960), new for the Italian fauna, and on some interesting species of Lepidoptera Tortricidae, are reported. P. suspectana, found in Molise region, was distributed in Central and Northern Europe, Caucasus and North-Western Africa. D. infuscata, found on the mountains of Central Appennine, was reported from Crimea and Caucasus. The presence in Italy of Lozotaeniodes formosanus (Geyer, 1830), Epinotia dalmatana Rebel, 1891, and Pammene oxycedrana (Millière, 1874) was confirrned.